Gaining access to agency and structure in industrial marketing theory: A critical pluralist approach. (December 2014) - Nicholson, John D.; Brennan, Ross; Midgley, Gerald
This article is concerned with gaining greater insight into the interplay between agency and structure in industrial marketing (IM) scholarship. The article's intent is to embed Midgley's notion of critical pluralism within this endeavour. The article commends the movement towards increased deployment of critical realism, but cautions against the dangers of creating further atomism in marketing theory by generating another paradigm of thought with strongly defended boundaries, impervious to outside influence. The article advances a case for critical pluralism within IM scholarship and offers a three-dimensional (theoretical, methodological and methodical) framework to aid this. The discussion demonstrates how critical pluralism can be deployed to gain insights into agency and structure using a number of 'integrative' theoretical perspectives.